Fiscal Decentralization and Poverty in Selected African Countries: A Case of Per Capital Index - (:unkn) unknown (My University, 2025)
This investigated how fiscal decentralization influences poverty in selected African countries from the implication of fiscal decentralization on per capita income of the citizens of the selected African countries. The study adopted an ex post facto research design, and data were collected from World Bank Indicators (WDI), the International Monetary Fund (IMF) fiscal decentralization database, and the World Governance Index (WGI) of ten selected African countries for a period of 18 years from 2006 to 2023 fiscal years. The study employed descriptive statistics and inferential regression analysis. Considering using the panel unit root test (PURT) of Levin, Lin, and Chu (LLC, 2002) and Im, Persaran, and Shin (IPS, 2003), the Augmented Dickey-Fuller (ADF) and the Philips-Perron (PP)-based tests were also tested as first-generation PURT. The panel regression analysis revealed that fiscal decentralization determinants had a significant effect on per capita income as a measure of poverty. The findings demonstrated that effective fiscal decentralization practice has the ability to enhance per capita income rating in Africa. The study recommended that governments at all levels should carefully explore and maximize true fiscal decentralization practices to improve the per capita income of their citizens.
Keywords: African Research